How Frustrated Lewis Acid/Base Systems Pass through Transition‐State Regions: H2 Cleavage by [tBu3P/B(C6F5)3]. Issue 14 (8th August 2014) - Pu, Maoping; Privalov, Timofei
Abstract We investigate the transition‐state (TS) region of the potential energy surface (PES) of the reaction tBu3P+H2+B(C6F5)3→tBu3P‐H(+)+(−)HB(C6F5)3 and the dynamics of the TS passage at room temperature. Owing to the conformational inertia of the phosphane⋅⋅⋅borane pocket involving heavy tBu3P and B(C6F5)3 species and features of the PES E(P⋅⋅⋅H, B⋅⋅⋅H | B⋅⋅⋅P) as a function of P⋅⋅⋅H, B⋅⋅⋅H, and B⋅⋅⋅P distances, a typical reactive scenario for this reaction is a trajectory that is trapped in the TS region for a period of time (about 350 fs on average across all calculated trajectories) in a quasi‐bound state (scattering resonance). The relationship between the timescale of the TS passage and the effective conformational inertia of the phosphane⋅⋅⋅borane pocket leads to a prediction that isotopically heavier Lewis base/Lewis acid pairs and normal counterparts could give measurably different reaction rates. Herein, the predicted quasi‐bound state could be verified in molecular collision experiments involving femtosecond spectroscopy.